Hydrology of the horseshoe crab nesting grounds at Pahang Coast, Malaysia - John, Akbar; Yunus, Kamaruzzaman; Khan Chowdhury, Ahmed Jalal; Kassim, Zaleha (Oriental Scientific Publishing Co., 2011)
Selected hydrological parameters at the nesting grounds of horseshoe crabs along the Pahang coast were determined. A complete year data from March 2010 to February 2011 was collected using advanced multiparameter meter model Hanna HI 9828 probe. The surface water temperature varied from 29.060C - 19.360C at Balok and 29.10C-15.080C at Pekan station with mean annual temperature of 24.08±2.910C at Balok and 22.97±3.260C at Pekan. Surface water salinity varied from 30.11ppt-2.09ppt at Balok and 33.45ppt – 3.38ppt at Pekan station with mean annual salinity of 17.9±10.63ppt at Balok and 20.5±10.04ppt at Pekan coastal waters. Seasonal fluctuation in the pH of the water varied from 8.65-6.61 at Balok station and 8.18-6.12 at Pekan station. Throughout the sampling period the coastal waters of both the sampling sites were well mixed. The Dissolved oxygen (DO) in the water varied from 7.75-4.21ml/L at Balok and 7.75ppt – 3.06ml/L at Pekan station with mean annual DO of 6.24±0.95ml/L at Balok and 5.76±1.08ml/L at Pekan coastal waters. Physicochemical parameters showed apparent seasonal fluctuation in the salinity of the surface water was observed in both the sampling stations (P < 0.05) while other parameters such as temperature, pH and dissolved oxygen did not vary significantly.